Performance implications of physical & mental growth of the young athlete - Gibson, B. (coachesinfo.com)
The extensive involvement in sport and physical activity is an integral part of western society. On many occasions sport has been described as a major social institution. The adult controlled sporting mediums largely caters for young people in the age range of 10-18 years off age and involves millions of children world wide. There are proponents of junior sport who view it as a miniature life situation where children can learn life-long skills that will enable them to tackle the tasks of later life more competently. Critics on the other hand counter by pointing out that the excessive physical and psychological demands placed on the young people in these programs are primarily designed to satisfy the egos of coaches and parents. In order to gain a balanced point of view one needs to carefully consider the physiological and psychological development of children in this age range and ensure that these factors are taken into account when designing and conducting sportingprograms for the young children. Contents: Physical development: - Physical growth and maturation - Effect of training and exercise on growth and development - Patterns of physical growth - The early and late maturer Conclusion The question of physical development remains a complex issue, and research has shown that it is affected by many factors. While it is essentially genetically controlled, it is also affected by environmental conditions. The influence of training on the developmental process is still open to debate, and more research is necessary before definite conclusions can be reached. A sound knowledge of processors of growth and development will enable coaches and teaches who are working with children, to organise the training programs that will be more beneficial to the children from a physical and psychological perspective. Psychological Development: - Why is the mental development of the young athlete so important? - Psychological and sociological considerations - Stages of psychological development - Why do children participate in youth sports? - Why do children drop out of sport? - What are the effects of organised sports? - Sporting myths - What can coaches do? - What can parents do? Conclusion: Competitive experiences are an important part of a child's development, and correctly managed it can be a very positive training ground for teaching one to compete successfully in the numerous areas that will confront them throughout life. The real value of competition will depend on how it is conducted. Parents and coaches have a very important role to play in ensuring that development and transition occurs in a manner that will maximize the young athletes' inherent potential and provide an enjoyable learning experience along the way.